Peripheral cemental caries in horses - Bengtström, Julia (2016)
During the past 15 years, equine dental practitioners in Sweden have experienced an increase in cemental caries. In 2002 a previously unknown bacteria, Streptococcus devriesei, was isolated from infundibular caries lesions. Between 2002 and 2009, all sampled Swedish horses with infundibular caries were positive for S. devriesei. An increasing number of negative controls with visually healthy cementum were also positive for the bacteria. The presence of SIgA (secretory immunoglobulin A) in saliva has been studied in horses with infundibular caries but the S. devriesei specific SIgA has not been proven to protect against infundibular caries. The oral microflora and SIgA levels of horses with peripheral caries lesions have not been studied before. Twenty-two horses with peripheral caries, 6 with infundibular caries and 3 negative controls were sampled for bacteriological analysis and SIgA levels. All but one were positive for S. devriesei. The bacterial levels did not correlate to the severity of the lesions. The 4 horses with the most severe peripheral caries lacked S. devriesei specific SIgA. Horses with high levels of total SIgA tended to also have high levels of S. devriesei specific SIgA.